2013
DOI: 10.6026/97320630009696
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of complex Histones Deacetylase (HDAC) Class II Homo Sapiens with suberoylanilide hydroxamic acid (SAHA) and its derivatives as inhibitors of cervical cancer

Abstract: Cervical cancer is second most common cancer in woman worldwide. Cervical cancer caused by human papillomavirus (HPV) oncogene. Inhibition of histone deacetylase (HDAC) activity has been known as a potential strategy for cancer therapy. SAHA is an HDAC inhibitor that has been used in cancer therapy but still has side effects. SAHA modification proposed to minimize side effects. Triazole attachment on the chain of SAHA has been known to enhance the inhibition ability of SAHA and less toxic. In this study, it wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The starting point of the development of our pipeline was the optimization of docking method, which would be improved later on [ 57 ]. Our experience in HPV drug design was based on design of organic compounds as drug candidates [ 46 , 58 ]. However, as carbon and boron based compounds have some similarity of physicochemical properties, the utilization of boron as carbon substitute for drug candidate becomes more feasible [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…The starting point of the development of our pipeline was the optimization of docking method, which would be improved later on [ 57 ]. Our experience in HPV drug design was based on design of organic compounds as drug candidates [ 46 , 58 ]. However, as carbon and boron based compounds have some similarity of physicochemical properties, the utilization of boron as carbon substitute for drug candidate becomes more feasible [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…ONYX-015, a E1B-55 kDa gene-deleted OA, in combination with chemotherapy has been assessed in phase I-II trials for patients with advanced cancer (26,27). The present study investigated the possibility of combining ZD55-TRAIL with SAHA, an HDAC inhibitor that may be a novel therapeutic agent for patients with cervical squamous cell carcinoma (14)(15)(16)28,29), in order to reinforce their antitumor activities. The present study demonstrated that subclinically achievable doses of SAHA (30), namely, 0.1-0.8 µM, significantly and synergistically increased ZD55-TRAIL oncotoxicity in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…However, as SAHA has certain side effects, we try to mitigate them by modifying its structure [16]. Hence, we have successfully generated SAHA derivatives and tested them by molecular docking and dynamics tools [27,28]. Hence, we elucidated the molecular interactions of the ligands in high-resolution graphics, as shown in figures 1 [29].…”
Section: In Silico Hpv Drug Developmentmentioning
confidence: 99%